Effect of thermal spring water on human dendritic cell inflammatory response - Eliasse Y; Galliano MF; Redoules D; Espinosa E (Dove Medical Press, 2019)
Yoan Eliasse1,2, Marie-Florence Galliano,3 Daniel Redoules,4 Eric Espinosa1,21INSERM U1037, Centre de Recherche en Cancérologie de Toulouse (CRCT), Toulouse F-31037, France; 2Université De Toulouse, Université Paul Sabatier, Toulouse F-31062, France; 3Research and Development, Pierre Fabre Dermo-Cosmétique, Toulouse, France; 4Global Medical Direction, Laboratoire Dermatologique Avène, Pierre Fabre Dermo-Cosmétique, Toulouse, FranceBackground: Hydrotherapy appears as a valuable therapeutic tool in the management of patients suffering from chronic skin inflammatory diseases. Nevertheless, the underlying immune mechanisms of these beneficial effects remain poorly understood. To better understand the biological effects of thermal spring water on the immune system, we investigated the effects of Avène thermal spring water (ASW) on dendritic cells as key cells participating in the control of the immune response.Methods: Dendritic cells (DCs) were generated from human monocytes and matured with LPS in ASW-based culture medium or in dexamethasone supplemented culture medium as an anti-inflammatory treatment. The phenotypes and abilities of these DCs to produce cytokines and induce allogeneic T cell response was next assessed.Results: We showed that ASW modulated the differentiation of monocytes into DCs and impacted the DC maturation upon LPS priming. We observed a reduction of the CD83, CD86, CD1a and HLA-DR molecule expression and a decrease of IL-12 and IL-23 production whereas IL-10 production was increased. LPS-primed DCs generated in presence of ASW exhibited a reduced capacity to induce naive CD4+, T cell proliferation and IFN-γ and IL-17 production.Conclusion: Our study showed that ASW is endowed with an immunomodulatory potential. ASW limits the DC stimulatory capacity of Th1 and Th17 cell responses by impairing their maturation, IL-12 and IL-23 production and accessory cell function.Keywords: dendritic cells, hydrotherapy, inflammation, naive CD4+, T cells, dexamethasone